Collective bargaining in Canada in the age of precarious employment. (3rd July 2021) - Lewchuk, Wayne
ABSTRACT: The decline in the prevalence of the Standard Employment Relationship in Canada has created challenges for Canadian unions. This article reviews the available estimates of the prevalence of precarious employment and gig work in Canada. Using data from the Poverty and Employment Precarity in Southern Ontario (PEPSO) research group it evaluates both the success of unions in organising workers in precarious employment and bargaining for them. The last section reviews recent union strategies to organise workers in precarious employment with a focus on the subset of precarious employment referred to as gig work. Organising gig workers presents unique challenges for unions as many are deemed by their employers as independent contractors and as a result not covered by existing Canadian labour legislation and hence not eligible for union membership. The paper concludes by arguing that organising precarious workers is a work in progress, whose ultimate outcome remains uncertain.